(3GdebfY aj CNJUGQ Yde CHj ebQYs - (3GdpepQrZJj , eMeO Hf SYjO Hf eMeO Hf jMji GdShSj, CHh YHO Gddg,J (B1089 (3g` s
(3ChdgG (B:s
(3bGd jbhd HYO MeO eLQi Gdadc Ke Ydi eMeO GdgGOi GdRci s
(3BNQgG (B:s
(3bO GfJgi GdeNJUQ GdebUhO hQHfG dGZjQg , GdeMehO SejJg GdebfY ai Yde CHj ebQY GHZ faY GeI eMeO GfJgi hGdMeO ddg s
(3Vef eLehY s
(3QLR ai Yde GdJhbjJ fXeI ai YGe (B1040 (3g`s
(3cJHJ Hbde ajg VHW hHgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B139 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B38s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B615 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B707 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdadcs